Debates and Discourses on Ornament in Contemporary Architecture - Deniz Balık Lökçe (DEPARCH Journal of Design Planning and Aesthetics Research)
This paper neither intends to construct a theoretical framework of the history of ornament nor focuses on its thresholds. Mainly, it aims to uncover the long-lost meanings of ornament by delving into the origins of the concept. It discusses the issue of “the function of ornament” today, mainly through The Function of Ornament (2006), edited by Farshid Moussavi and Michael Kubo. This book distinguishes itself from other current publications because it is one of the first works to discuss ornament from a new viewpoint by graphically analyzing a variety of twentieth and twenty-first-century buildings in terms of form, screen, structure, and surface. The book shows that ornament, as an integral element, is integrated to material, structure, and form, rather than being extrinsic and additional, which brings us to the etymology and the origins of the term. Thus, this paper explores what is considered as new in terms of ornament in contemporary architecture by analyzing case studies from the book.